2018
DOI: 10.1177/1534735418809901
|View full text |Cite
|
Sign up to set email alerts
|

Rhazyaminine from Rhazya stricta Inhibits Metastasis and Induces Apoptosis by Downregulating Bcl-2 Gene in MCF7 Cell Line

Abstract: Background: The role of alkaloids isolated from Rhazya stricta Decne (Apocynaceae family) (RS) in targeting genes involved in cancer and metastasis remains to be elucidated. Objective: Identify and characterize new compounds from RS, which inhibit gene(s) involved in the survival, invasion, self-renewal, and metastatic processes of cancer cells. Methods: Bioinformatics study was performed using HISAT2, stringtie, and ballgown pipeline to understand expressional differences between a normal epithelial cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Our earlier studies have also demonstrated that medicinal plant R stricta is an important resource for discovering and isolating novel compounds with potential anticancer activity. 4,36…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies have also demonstrated that medicinal plant R stricta is an important resource for discovering and isolating novel compounds with potential anticancer activity. 4,36…”
Section: Discussionmentioning
confidence: 99%